2016
DOI: 10.24914/jeb.v19i1.483
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Permodalan Bank Melalui Profitabilitas, Risiko, Ukuran Perusahaan, Efisiensi Dan Struktur Aktiva

Abstract: <p align="center"><em>This study analyzes the influence of causality between the CAR, profitability, risk</em><em>, company size, efficiency and as</em><em>s</em><em>et structure</em><em> of the banking industry. The sampling technique used in this research is purposive sampling, with the criteria of banks have gone public before 2008, publish the financial statements for 2008-2013. The total sample of 23 banks. The purpose of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
0
8
0
7
Order By: Relevance
“…Several previous studies measuring bank performance tended to be based on financial ratios, namely the concept of profitability (Fitriana, Rosyid, & Fakhrina, 2015;Gambacorta, 2017;Tarazi & Zedek, 2014;Haryanto, 2016;Thalib, 2016). Profitability is more proxied by Return on Assets (ROA), which compares the net income to bank assets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies measuring bank performance tended to be based on financial ratios, namely the concept of profitability (Fitriana, Rosyid, & Fakhrina, 2015;Gambacorta, 2017;Tarazi & Zedek, 2014;Haryanto, 2016;Thalib, 2016). Profitability is more proxied by Return on Assets (ROA), which compares the net income to bank assets.…”
mentioning
confidence: 99%
“…Several concepts and variables emerged as determinants of SGR from some previous researchers, namely LDR which is currently LFR as a proxy for liquidity (Atemnkeng & Nzongang, 2006;Yuliani, 2007;Respati & Yandono, 2008;Mintarti, 2009;Amouzesh et al, 2011;Ahmad, 2015;Firdausi, 2016;Haryanto, 2016;Thalib, 2016). Research (Zulkifli et al, 2018) on the determinants of LFR using 10 commercial banks on the Indonesia Stock Exchange with the 2011-2016 period with a total N sample of 60 observations found that the determinant of LFR was CAR and NPL while BOPO had no significant effect on LFR.…”
mentioning
confidence: 99%
“…Sehingga kebijakan struktur modal akan berimplikasi pada kinerja perusahaan. Kebijakan struktur modal akan berdampak pada kinerja peru-sahaan (Subagyo, 2011;Nugraha, 2013;Komara, Hartoyo dan Andati, 2014;Haryanto, 2016).…”
Section: Pendahuluanunclassified
“…Penelitian yang menginvestigasi hubungan antara ukuran perusahaan antara lain dilakukan Haryanto (2016) menunjukkan bahwa ukuran perusahaan berpengaruh positif terhadap struktur modal perusahaan. Namun penelitian Christianti (2006) menunjukkan ukuran perusahaan berpengaruh negatif terhadap struktur modal.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation